Beyond Early Infant Diagnosis: Changing the Approach to HIV-Exposed Infants. (15th August 2018) - Modi, Surbhi; Broyles, Laura N.; Montandon, Michele; Itoh, Megumi; Ochanda, Boniface; Langat, Agnes; Sullivan, David; Dale, Helen
Abstract : Abstract: Despite dramatic global progress with implementing prevention of mother-to-child HIV transmission (PMTCT) programs, there were 160, 000 new pediatric HIV infections in 2016. More than 50% of infant HIV infections now occur in the postpartum period, reflecting the relatively high coverage of interventions in the antenatal period and the need for greater attention to the breastfeeding mother and her HIV-exposed infant (HEI). Early diagnosis and treatment are critical to prevent morbidity and mortality in HIV-infected children; however, early infant HIV testing rates remain low in most high HIV-burden countries. Furthermore, systematic retention and follow-up of HEI in the postpartum period and ascertainment of final HIV status remain major program gaps. Despite multiple calls to action to improve infant HIV testing rates, progress has been marginal due to a lack of focus on the critical health care needs of HEI coupled with health system barriers that result in fragmented services for HIV-infected mothers and their families. In this paper, we describe the available evidence on the health outcomes of HEI, define a comprehensive care package for HEI that extends beyond early HIV testing, and describe successful examples of integrated services for HEI.